The perspectives of individuals with incomplete spinal cord injury on measuring the intensity of balance challenge during reactive balance training: A qualitative study - Matthew G. Heffernan; Anna Ogonowska-Slodownik; Alyssa Benitez; Katherine Chan; Elizabeth L. Inness; Kristin E. Musselman (PLoS ONE, 2026)
Importance Balance rehabilitation is an important component of recovery for individuals with incomplete spinal cord injury (iSCI), who are at heightened risk of falls due to impaired postural control. Intensity of balance challenge refers to the postural control demand of a task relative to an individual’s maximum capacity. Achieving adequate intensity of balance challenge is essential for appropriate prescription of balance exercises. Balance intensity is often assessed through self-report on an ordinal scale. However, there is limited understanding of how individuals with iSCI interpret the concept of balance intensity and use self-reported scales. Design A qualitative descriptive study was conducted. Twelve individuals with iSCI (nine male, three female; mean age 67.2 ± 12.9 years) participated while undergoing Reactive Balance Training. Over six weeks, participants rated the balance challenge intensity of each exercise using an 11-point ordinal scale. Once per session, participants explained their ratings to a researcher who recorded the comments as field notes. After completing ≥10 training sessions, participants completed a semi-structured interview exploring their definitions of balance challenge, factors influencing their difficulty ratings, and their views on the Balance Intensity Scale, an alternative measure used with older adults. Interviews were audio recorded, transcribed verbatim, and analyzed alongside field notes using a conventional content analysis. Results Five themes were identified: 1) Influence of task familiarity on perceived balance challenge, 2) Influence of fear of falling on perceived balance challenge, 3) Misuse of ordinal scale, 4) Ambiguity of ordinal scale, and 5) Concern of the time demand of scales. Participants are concerned about lost training time and value clinician expertise over their self-reported rating for efficient assessment. Conclusions Participants’ perspectives on measuring balance intensity highlight the complexity of this concept. Future work could employ quantitative evaluations of the validity of self-reported balance intensity and consider the tools/skills used by clinicians.